Skyscrapers and the economy in Latin America. Issue 4 (1st October 2016) - Garza, Nestor; Lizieri, Colin
Abstract: Skyscrapers are an intellectual challenge for urban analysis because of their imposing visual presence in the city landscape, and because of their environmental and real estate impacts. These characteristics however have not received much attention in the literature, particularly in analyses about Latin American cities. In this paper, we describe and test four theories about record-breaking buildings height: traditional microeconomic theory, game theory, business cycle, and global cities. We use a 2000–2012 panel database of 29 cities from 10 different Latin American countries, in order to contrast the contesting explanations about buildings' height. We design a baseline model and then, using four different estimation techniques and diverse specifications, find that traditional theory and more strongly, global cities are good predictors of buildings' height.